Fe(iv) alkylidenes via protonation of Fe(ii) vinyl chelates and a comparative Mössbauer spectroscopic study1. Issue 8 (14th August 2015) - Lindley, Brian M.; Swidan, Ala'aeddeen; Lobkovsky, Emil B.; Wolczanski, Peter T.; Adelhardt, Mario; Sutter, Jörg; Meyer, Karsten
<x xml:space="preserve">Abstract</x> Fe(iv) alkylidenes are produced via protonation of Fe(ii) vinyl chelate complexes.